Influence of solubilizer PEG-40 hydrogenated castor oil on carbopol gels' structural-mechanical properties - Ye. V. Gladukh; І. М. Grubnik; Н. Р. Kukhtenko (Zaporozhye State Medical University, 2017)
Rheological properties affect all stages of the drug development - from development to production, the characteristics of the final products and stability. A lot of substances have complex rheological properties; their viscosity and elasticity can vary depending on conditions acting from the outside, such as stress, deformation, time factor and temperature. Concentration, stability and composition also significantly affect the rheological properties of drugs. One of the current trends in modern pharmacy is the development of drugs in the form of gels. The rheological properties of gels are significantly influenced by surface-active substances, stabilizers, solubilizers, stabilizing their structure. A special group of stabilizers are hydrogenated vegetable oils and their compounds with polymers, which have the ability to structure formation in interphase layers and in the volume of phases. For this purpose, PEG-40 hydrogenated castor oil is widely used. The aim of this work is to study the effect of hydrogenated castor oil, used as an emulsifier, solubilizer, viscosity modifier and solvent in the technology of semisolid dosage forms, on the structural and mechanical properties of carbopol gels. Materials and methods. 1% gel carbopol with additives PEG-40 hydrogenated castor oil in the concentration range from 1 to 5 % was investigated as experimental samples of the gel base. A 10 % propylene glycol additive was used as humectant and plasticizer. Structural and mechanical studies were carried out using a rotational viscometer «RheolabQC», Anton Paar (Austria) with coaxial cylinders CCC27/SS. The graphs of the gels were automatically plotted using the computer program. Results. Analysis of the rheological parameters of the carbopol with PEG-40 hydrogenated castor oil gel base shows that the solubilizer has an active influence on the structural and mechanical properties of the base. Addition of PEG-40 GMM to the carbopol gel increases the yield strength by 53 % (to 188.22 Pa at 5 % PEG-40 GKM injection), reduces the value of the yield strength of the base to 337.0-374.0 Pa s and, accordingly, increases the structure breakdown from 1.56 Up to 2.39 Pa s with an increase in the shear rate to 350 s-1, increases the hysteresis loop to 22525.9 Pa/s while reducing the stability of the system by more than 2 times and increases the value of mechanical stability to 1.16-1.37, that at the end can affect the deterioration of the restoration of the structure after deformation. Conclusions. Was studied the effect of the solubilizer PEG-40 hydrogenated castor oil on the structural and mechanical properties of carbopol gels using the «RheolabQC», Anton Paar rotary viscometer. It has been found that the use of this solubilizer in excess of 5 % is impractical due to the deterioration of the rheological properties of the gel, a decrease in mechanical stability and a decrease in the consumer qualities of the drug.